EDUKASI PENGELOLAAN SAMPAH DENGAN KONSEP 3R (REDUCE, REUSE, RECYCLE) DI SMP NEGERI 30 SIGI - Matius Paundanan; Robert V. Pelima; Rikwan Rikwan; Sitti Fajrah; Fitriani Fitriani; Fitri Arni HR (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Waste is the residual product of human activities in everyday life that is no longer used, disliked or even thrown away. The existence of waste that is left scattered in the environment can have an impact on environmental and human health. This is because waste can become a breeding ground for disease vectors, such as rats, flies and mosquitoes which can cause diarrhea and dengue fever. Household scale waste management can be done using the 3R method (Reduce, Reuse and Recycle). Waste management with the 3R principle can not only reduce the amount of waste, but also has economic value by becoming an alternative source of income for the community. The purpose of this activity is to increase students' understanding of the impact of waste and waste management and to foster a character of love for the environment in students. The form of this community service activity is in the form of counseling or health education on how to process waste with the 3 R principles (Reduce, Reuse, Recycle) at SMP Negeri 30 Sigi. The results of the evaluation show that participants can understand the material presented. This can be seen during the discussion session where the participants were very enthusiastic in asking and answering questions when giving quizzes